Caregivers’ quality of life in mild and moderate dementia - Raquel Luiza Santos; Maria Fernanda Barroso de Sousa; José Pedro Simões-Neto; Marcela Lima Nogueira; Tatiana T. Belfort; Bianca Torres; Rachel Dias Lopes da Rosa; Jerson Laks; Marcia Cristina Nascimento Dourado (Arquivos de Neuro-Psiquiatria)
Objective To investigate quality of life (QoL) of caregivers of mild and moderate dementia and the aspects related to QoL. Method Cross-sectional assessment of dyads of people with dementia (PwD) and family caregivers (n=88). Results Burden (p<0.05) and depressive symptoms (p<0.001) were related to caregivers’ QoL in both stages of dementia. In mild dementia, caregivers’ depressive symptoms (p<0.001) and PwD neuropsychiatric symptoms (p<0.001) were related to burden. PwD aberrant motor activity (p<0.001) and anxiety (p<0.001), and caregiver-reported QoL domains of friends (p<0.001) and mood (p<0.05) were related to depressive symptoms. In moderate dementia, self-reported QoL (p<0.01) and anxiety (p<0.01), and PwD anxiety (p<0.01) were related to burden. Caregivers’ anxiety (p<0.001) and self-reported QoL (p<0.001) were related to depressive symptoms. Conclusion Burden and depressive symptoms were related to QoL of caregivers of mild and moderate dementia. However, they are driven by different factors according to dementia severity.